DNA methylation dynamics in a coastal foundation seagrass species under abiotic stressors. Issue 1991 (25th January 2023) - Pazzaglia, Jessica; Dattolo, Emanuela; Ruocco, Miriam; Santillán-Sarmiento, Alex; Marin-Guirao, Lazaro; Procaccini, Gabriele
Abstract : DNA methylation (DNAm) has been intensively studied in terrestrial plants in response to environmental changes, but its dynamic changes in a temporal scale remain unexplored in marine plants. The seagrass Posidonia oceanica ranks among the slowest-growing and longest-living plants on Earth, and is particularly vulnerable to sea warming and local anthropogenic pressures. Here, we analysed the dynamics of DNAm changes in plants collected from coastal areas differentially impacted by eutrophication (i.e. oligotrophic, Ol; eutrophic, Eu) and exposed to abiotic stressors (nutrients, temperature increase and their combination). Levels of global DNAm (% 5-mC) and the expression of key genes involved in DNAm were assessed after one, two and five weeks of exposure. Results revealed a clear differentiation between plants, depending on environmental stimuli, time of exposure and plants' origin. % 5-mC levels were higher during the initial stress exposure especially in Ol plants, which upregulated almost all genes involved in DNAm. Contrarily, Eu plants showed lower expression levels, which increased under chronic exposure to stressors, particularly to temperature. These findings show that DNAm is dynamic in P. oceanica during stress exposure and underlined that environmental epigenetic variations could be implicated in the regulation of acclimation and phenotypic differences depending on local conditions.